Public Relations: A Tool for Scaffolding Effective Communication Between Moroccan University Professors and Higher Education Administrators - ACHAARI, SAD (International Journal of Language and Literary Studies, 2022)
The present study investigates how Public Relations can upgrade effective communication between university professors and higher education administrators. The data was collected through a questionnaire handed out to 135 Moroccan university professors and administrators operating in more than 10 Moroccan public higher institutions. This study aims to show the importance of public relations communication as a propitious tool conducive to quality in higher education. The results of this study corroborate that the Moroccan university professors ’interaction with higher education administration is mainly compatible with some elements of public relations communication. The results also show that Moroccan university professors and higher education administrators are aware of the positive impact of effective communication on the university’s reputation and the good functioning of the teaching and scientific research at the tertiary level. The findings also reveal some aspects that hinder effective communication between university professors and administrators.